SOILS OF THE EASTERN PRIOL’KHONYE ON THE COAST OF THE LAKE BAIKAL: CURRENT STATE AND USE - I. A. Belozertseva; D. N. Lopatina; N. A. Zvereva (Бюллетень Почвенного института им. В.В. Докучаева)
In summer periods of 2015–2017 within the framework of complex expeditions in the eastern Priol’khonye soil geochemical researches were performed. More than 120 soil samples were collected for subsequent physical and chemical analyses. Ecological, chemical and physical properties of meadow and steppe soils of Ol’khon district were studied and the results are presented in the article. The research was conducted on the east coast of the Lake Baikal in its central basin, which is most visited by tourists. Several soil types can be found along the coast line and on gently sloped surface nearby, they are: castanozems, umbrisols, cambisols, gray soils, histic fluvisols gleyic, humic fluvisols gleyic, chernozems, umbric fluvisols, cambic fluvisols and other. Owing to a specific environmental conditions some original soil types (for example “chestnut soils”, “castanozems”) can be found nowhere else in the Irkutsk region but only here. The explored soil profiles are mainly thick and stony to various extent (from high to medium),these soils are sandy or sandy loams, rich in humus, predominantly with neutral and weakly alkaline reaction (pH), low content of nitrogen in relation to carbon content (C : N), that creates favorable conditions for preservation of the vegetable remains in meadow landscapes. The conducted research results revealed that soils near touristic tracks and also on the territory of the ancient settlement are polluted by heavy metals, and their content exceeds sanitary and hygienic standards. The ecological condition of soils at the present stage can be characterized as average degree of disturbance resulting from recreational activity. Geochemical barriers are represented by organic and alkaline ones. However, due to the sandy and sandy-loamy soil texture waters of the lake coastal zone can be polluted by heavy metals as well. Soils of meadow-boggy landscapes of the coastal area are not polluted by heavy metals as far as it is a hard-to-reach region for tourists using automobile transport.